Social Media, Public Health Research, and Vulnerability: Considerations to Advance Ethical Guidelines and Strengthen Future Research - Philip M Massey; Regan M Murray; Shawn C Chiang; Alex M Russell; Michael A Yudell (JMIR Publications, 2023)
The purpose of this article is to build upon prior work in social media research and ethics by highlighting an important and as yet underdeveloped research consideration: how should we consider vulnerability when conducting public health research in the social media environment? The use of social media in public health, both platforms and their data, has advanced the field dramatically over the past 2 decades. Applied public health research in the social media space has led to more robust surveillance tools and analytic strategies, more targeted recruitment activities, and more tailored health education. Ethical guidelines when using social media for public health research must also expand alongside these increasing capabilities and uses. Privacy, consent, and confidentiality have been hallmarks for ethical frameworks both in public health and social media research. To date, public health ethics scholarship has focused largely on practical guidelines and considerations for writing and reviewing social media research protocols. Such ethical guidelines have included collecting public data, reporting anonymized or aggregate results, and obtaining informed consent virtually. Our pursuit of the question related to vulnerability and public health research in the social media environment extends this foundational work in ethical guidelines and seeks to advance research in this field and to provide a solid ethical footing on which future research can thrive.